Relationship between dental anxiety, dental utilization, and oral health-related quality of life: a systematic review - Ab Malek, Azizi; Mohd Radzi, Nawwal Alwani; Che Musa, Muhd Firdaus; Luai, Amirul Faiz (Wolters Kluwer - Medknow, 2024)
Aim: No comprehensive synthesis of dental anxiety (DA), dental utilization (DU), oral health-related quality of life (OHRQoL), and their relationships have been examined despite various systematic investigations being done on their prevalence and interventions individually. Therefore, this review aims to systematically review the status and relationship between DA, DU, and OHRQoL among adult groups. Materials and Methods: Data collection spanned 6 months, from 1 July to 31 December 2023, involving eight databases. Only cross-sectional (CS) studies with adult participants aged 15–64 years, conducted globally, published in English, and available as full-text articles by December 31, 2023, were included. Two reviewers screened the titles and abstracts and assessed the full-text articles. All studies were CS. The risk of bias was evaluated using the Joanna Briggs Institute’s Critical Appraisal Checklist for Analytical CS studies. The quality of evidence for each measured factor was assessed using the Grading of Recommendations Assessment, Development, and Evaluation methodology. Results: The initial search yielded 3333 studies. The 22 final studies included 13 high quality studies with over 80% and nine fair studies with 50% and 79% scored. None of the studies scored below 50%. A negative link between DA and DU was identified in 15 of 16 studies with 35,846 participants aged 22.19–50.21 years. Six studies on DA, DU, and OHRQoL included 22,845 participants aged 15–55 years, mostly in their late and mid-fifties. Four of six verified Berggren and Meynert’s (1984) vicious cycle theory’s high association between DA, DU, and OHRQoL. Conclusions: A 22-study review reveals a strong association between DA, DU, and OHRQoL. Most moderate to high-quality studies emphasized a negative correlation between DA and DU, which affected OHRQoL. PROSPERO registration number CRD42023455219.